Individual Experience and Home Price Expectations - Fang, Shuai; Liu, Xiaolong; van der Vlist, Arno J. (Journal of Financial and Quantitative Analysis, 2025)
Abstract We examine whether the heterogeneity of expectations is associated with idiosyncratic variations in experience. Combining household survey data and administrative data from the Netherlands, we find that given market development, households’ expectations about house price changes vary with their individual experience. This association is related to the use of information conveyed by experience, which varies in terms of informativeness, recency, and household sophistication. Finally, we find that individual experience also explains how far house price expectations deviate from realized house prices and that it may affect household behavior. Our findings elucidate the role that individual experience plays in expectation formation.